2019
DOI: 10.1111/1758-2229.12811
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the acetogenic bacterium Acetobacterium woodii by dismutation of acetaldehyde to acetate and ethanol

Abstract: Acetogenic bacteria are a group of strictly anaerobic bacteria that may have been first life forms on Earth since they employ an ancient pathway for CO 2 fixation into acetyl-CoA that is coupled to the synthesis of ATP, the Wood-Ljungdahl pathway. Electrons for CO 2 reduction are derived from oxidation of H 2 or CO and thus, these bacteria can grow lithotrophically on gases present on early Earth. Among the organic molecules present on early Earth is acetaldehyde, a highly volatile C2 compound. Here, we demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Interestingly, induction by acetaldehyde was mere 2-fold higher than in the control where no inducer was added (formate only). Since the first step in metabolism of acetaldehyde by A. woodii involves the key enzyme AdhE to produce ethanol and acetyl-CoA ( Trifunovic et al, 2020 ), it might be the case that ethanol is the actual inducer of pdu operon during growth on acetaldehyde. Since the reporter gene assay was carried out in a 24 h time frame and no growth was observed on addition of acetaldehyde, possibly low ethanol formation resulted in low induction of the reporter gene.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, induction by acetaldehyde was mere 2-fold higher than in the control where no inducer was added (formate only). Since the first step in metabolism of acetaldehyde by A. woodii involves the key enzyme AdhE to produce ethanol and acetyl-CoA ( Trifunovic et al, 2020 ), it might be the case that ethanol is the actual inducer of pdu operon during growth on acetaldehyde. Since the reporter gene assay was carried out in a 24 h time frame and no growth was observed on addition of acetaldehyde, possibly low ethanol formation resulted in low induction of the reporter gene.…”
Section: Discussionmentioning
confidence: 99%
“…Acetogens are metabolically very versatile and can also grow heterotrophically on sugars, carboxylic acids and aldehydes (Bache & Pfennig, 1981; Drake et al, 2008; Gößner et al, 1994; Moon et al, 2019; Seifritz et al, 1999; Trifunovic et al, 2020; Weghoff et al, 2015). Actually, the WLP was discovered during glucose fermentation in Moorella thermoacetica (formerly Clostridium thermoaceticum ; Fontaine et al, 1942).…”
Section: Introductionmentioning
confidence: 99%
“…Our earlier studies have shown that BMCs are not only produced during growth on 1,2‐PD but also during heterotrophic growth of A. woodii on ethanol (Bertsch et al ., 2016), acetaldehyde (Trifunovic et al ., 2020), 2,3‐butanediol (2,3‐BD) (Hess et al ., 2015), ethylene glycol (Trifunović et al ., 2016) or fructose (Schuchmann et al ., 2015). During growth on many of these substrates, alcohol dehydrogenases apparently play an important role.…”
Section: Resultsmentioning
confidence: 99%
“…During growth on many of these substrates, alcohol dehydrogenases apparently play an important role. While the A. woodii genome encodes 11 putative Adhs, only the bifunctional AdhE has been purified and characterized to be the key enzyme involved in ethanol and acetaldehyde metabolism of A. woodii (Bertsch et al ., 2016; Trifunovic et al ., 2020). However, during growth on either 1,2‐PD or 2,3‐BD, AdhE was not produced by A. woodii .…”
Section: Resultsmentioning
confidence: 99%